Gender and Development Mainstreaming : Country Gender Assessment 2012, Philippines - World Bank (Washington, DC, 2014)
Just as development means less poverty or better access to justice, it also means fewer gaps in wellbeing between males and females. Women's empowerment and gender equality are development objectives in their own right, as embodied in the Millennium Development Goals. It is espoused as well in the Convention on the Elimination of All Forms of Discrimination against Women (CEDAW), ratified by the Philippines in 1981; the convention established a comprehensive framework for the advancement of women and has been mainstreamed in the Magna Carta of Women, RA 9710. Gender equality is smart economics: it can enhance economic efficiency and improve other development outcomes in three ways: first, removing barriers that prevent women from having the same access as men to education, economic opportunities, and productive inputs can generate broad productivity gains. Second, improving women's absolute and relative status contributes too many other development outcomes, including those for their children. Third, leveling the playing field, where women and men have equal chances to become socially and politically active, make decisions, and shape policies, is likely to lead to more representative, and more inclusive, institutions and policy choices and thus to a better development path.